2015
DOI: 10.1002/pon.3899
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the extended parallel process model in promoting colorectal cancer screening

Abstract: Objective: Relatives of colorectal cancer (CRC) patients are at increased risk for the disease, yet screening rates still remain low. Guided by the Extended Parallel Process Model, we examined the impact of a personalized, remote risk communication intervention on behavioral intention and colonoscopy uptake in relatives of CRC patients, assessing the original additive model and an alternative model in which each theoretical construct contributes uniquely.Methods: We collected intention-to-screen and medical re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(71 citation statements)
references
References 33 publications
3
67
1
Order By: Relevance
“…This result does not support the finding from Birmingham et al (2015) whose results indicated that motivation to screen was significantly associated with colonoscopy uptake. However, the result from the current study is similar to previous research which has suggested that people with positive intentions often fail to actually perform the behaviour (Webb & Sheeran, 2006).…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…This result does not support the finding from Birmingham et al (2015) whose results indicated that motivation to screen was significantly associated with colonoscopy uptake. However, the result from the current study is similar to previous research which has suggested that people with positive intentions often fail to actually perform the behaviour (Webb & Sheeran, 2006).…”
Section: Discussioncontrasting
confidence: 99%
“…Guided by the EPPM, Birmingham et al (2015) examined the impact of a personalised, remote risk communication intervention on behavioural intention and colonoscopy uptake in relatives of CRC patients, assessing the original additive EPPM model and an alternative model in which each theoretical construct contributed uniquely. The intervention involved participants receiving tailored print materials and a cancer risk assessment and counselling telephone call by a genetic counsellor.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations